Contribution of macromolecules to brain 1H MR spectra: Experts' consensus recommendations. (25th November 2020) - Cudalbu, Cristina; Behar, Kevin L.; Bhattacharyya, Pallab K.; Bogner, Wolfgang; Borbath, Tamas; de Graaf, Robin A.; Gruetter, Rolf; Henning, Anke; Juchem, Christoph; Kreis, Roland; Lee, Phil; Lei, Hongxia; et al.
Abstract : Proton MR spectra of the brain, especially those measured at short and intermediate echo times, contain signals from mobile macromolecules (MM). A description of the main MM is provided in this consensus paper. These broad peaks of MM underlie the narrower peaks of metabolites and often complicate their quantification but they also may have potential importance as biomarkers in specific diseases. Thus, separation of broad MM signals from low molecular weight metabolites enables accurate determination of metabolite concentrations and is of primary interest in many studies. Other studies attempt to understand the origin of the MM spectrum, to decompose it into individual spectral regions or peaks and to use the components of the MM spectrum as markers of various physiological or pathological conditions in biomedical research or clinical practice. The aim of this consensus paper is to provide an overview and some recommendations on how to handle the MM signals in different types of studies together with a list of open issues in the field, which are all summarized at the end of the paper. Abstract : This paper gives an overview of mobile macromolecules (MM) and provides recommendations on how to handle MM signals in different types of studies. A list of open questions to be investigated in the future is also provided.